A robust optimization approach for coordinated operation of multiple energy hubs. (15th April 2020) - Lu, Xinhui; Liu, Zhaoxi; Ma, Li; Wang, Lingfeng; Zhou, Kaile; Yang, Shanlin
Abstract: The energy hub (EH) has become an important concept in terms of optimizing multi-carrier energy systems' efficiency and flexibility. In this regard, an optimal operation model for managing multiple EHs with electrical and heat energy demands is proposed, which aims to reduce the total cost of the EHs. The components of each EH include the combined heat and power (CHP) unit, gas boiler, heat storage (HS) unit, wind turbine (WT) and photovoltaic (PV) array. A robust optimization approach is then proposed to deal with the uncertainties of renewable distributed energy resources (RDERs) and electricity prices. Meanwhile, both electrical and thermal demand response (DR) programs are considered in the proposed model. Finally, the optimized dispatch results under three different scheduling scenarios, i.e., the independent scenario, and the aggregation scenarios with and without DR programs are discussed. The simulation results show that the proposed multiple EHs optimization model can effectively reduce the total cost of EHs. Meanwhile, the results also reveal that implementing the DR programs can further reduce the consumers' total costs through load shifting. Highlights: An optimal operation model for managing multiple energy hubs is proposed. Both electrical and thermal demand response programs are taken into account. The uncertainties of the renewable energy and electricity prices are considered. A robust optimization approach is proposed to deal with the uncertainties. The dispatch results under three different scheduling scenarios are discussed.